Navigating the Transformative Impact of Artificial Intelligence on English Language Teaching: Exploring Challenges and Opportunities - Idham, Afif Zuhdy; Rauf, Wahyuddin; Rajab, Abd. (Universitas Muhammadiyah Barru, 2024)
This study aims to examine the impact of artificial intelligence (AI) on English language teaching in higher education. The scope of the study was limited to the opportunities and challenges of English language teaching. This study was conducted using a mixed method of conducting surveys and in-depth interviews. A questionnaire link using Spreadsheet’s Google Form was sent to the English lecturer through the WhatsApp group and personal contact No. The study sample consisted of 16 English lecturers. Analyzing the questionnaire and interview transcript indicates that the emergence of artificial intelligence (AI) technology has created opportunities and challenges for English language teaching and learning. AI has changed the landscape of English language teaching in higher education. English lecturers utilized different types of AI for various purposes, for example, asking and solving questions and checking for grammatical errors, checking plagiarism, paraphrasing, and reviewing literature. The study also revealed that AI has a variety of advantages for language teaching and learning, including the detection of plagiarism and grammatical errors. In addition, AI has created opportunities and challenges for the future of English language teaching. AI required digital literacy to utilize. The English teaching profession might be taken over by AI in the future, so English lecturers must continuously improve their digital literacy.